2010
DOI: 10.1593/neo.10344
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxic Tumor Microenvironments Reduce Collagen I Fiber Density

Abstract: Although the mechanisms through which hypoxia influences several phenotypic characteristics such as angiogenesis, selection for resistance to apoptosis, resistance to radiation and chemotherapy, and increased invasion and metastasis are well characterized, the relationship between tumor hypoxia and components of the extracellular matrix (ECM) is relatively unexplored. The collagen I (Col1) fiber matrix of solid tumors is the major structural part of the ECM. Col1 fiber density can increase tumor initiation, pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
79
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 75 publications
(84 citation statements)
references
References 45 publications
4
79
0
1
Order By: Relevance
“…Collagen is the major structural component in the formation of solid tumours and collagen fibre density can contribute to tumour initiation, invasion and metastasis (Gao et al 2010, Kakkad et al 2010. It has been shown that the increased expression of lysyl oxidase (LOX), an enzyme that covalently crosslinks collagen and elastin, is responsible for excess collagen deposition and hypoxiainduced metastasis of lung cancer through induction of b1 integrin signalling (Gao et al 2010).…”
Section: Ecm As Tumour Microenvironmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Collagen is the major structural component in the formation of solid tumours and collagen fibre density can contribute to tumour initiation, invasion and metastasis (Gao et al 2010, Kakkad et al 2010. It has been shown that the increased expression of lysyl oxidase (LOX), an enzyme that covalently crosslinks collagen and elastin, is responsible for excess collagen deposition and hypoxiainduced metastasis of lung cancer through induction of b1 integrin signalling (Gao et al 2010).…”
Section: Ecm As Tumour Microenvironmentmentioning
confidence: 99%
“…It has been shown that the increased expression of lysyl oxidase (LOX), an enzyme that covalently crosslinks collagen and elastin, is responsible for excess collagen deposition and hypoxiainduced metastasis of lung cancer through induction of b1 integrin signalling (Gao et al 2010). Kakkad et al (2010) also report that hypoxia causes reduction of collagen I fibre density and restructuring of the ECM, thus contributing to the tumour cell dissemination.…”
Section: Ecm As Tumour Microenvironmentmentioning
confidence: 99%
“…Snapfrozen primary breast tumor specimens were placed in Tissue Tek OCT freezing compound (Sakura Finetek USA), cryosectioned with a microcryotome (Microm International) at 100-μm thickness for whole-mount sections and 5-μm thickness for adjacent sections, fixed with 4% paraformaldehyde (Sigma-Aldrich) solution, stained for nuclei with Hoechst 33342 (Invitrogen, Carlsbad, CA), and mounted with Faramount aqueous mounting medium (DakoCytomation) as previously described. 19 For testing the within-tumor consistency of SHG-detected Col1 interfiber distances and Col1 fiber volume, we obtained FFPE samples from four different biopsy passes of the same breast cancer for four human specimens, which were grade 3,…”
Section: Breast Cancer Specimensmentioning
confidence: 99%
“…3,4,18 We have performed a small retrospective SHG microscopy study to determine if the Col1 fiber signature in primary breast tumors is altered in patients presenting with lymph node metastasis (LN þ ) compared to patients with uninvolved lymph nodes (LN − ). We used our in-house automated fiber analysis software as previously described, 19 which is free of user variability, and observed that primary breast cancers in LN þ patients have significantly denser Col1 fiber signatures than primary breast cancer in LN − patients. To validate our in-house software results, we additionally used two commonly used texture analysis techniques to analyze Col1 images: [20][21][22] the gray level co-occurrence matrix (GLCM) and the Fourier transform (FT).…”
Section: Introductionmentioning
confidence: 99%
“…Although proline can be obtained from the dietary proteins, an important source of proline is from the degradation of collagen in the ECM by sequential enzymatic catalysis of matrix metalloproteinases (MMPs) and prolidase [9,23]. The upregulation of MMPs in tumors has been considered a critical step for tumor progression and invasion [24][25][26]. A number of reports have shown that proline concentration is increased in various tumors, which may result from the upregulated MMPs degrading collagen.…”
Section: Proline Availability In Tumor Microenvironmentmentioning
confidence: 99%